Competitive disadvantages in producing and providing to Santa Rosa and Piedra Liza flowers markets - Venegas Palacios, Edgard (2014)
Managing the production of flowers has some shortcomings in marketing and there is no suitable distribution. In this work, a study was conducted from providing flowers to Santa Rosa and Piedra Liza markets, which the commercialization of this product is concentrated in Lima, from the same subjacency the respective supply chain is studied. The results will show recommendations for improving the production and marketing.